Changes in Cataplexy Frequency in a Clinical Trial of Lower-Sodium Oxybate with Taper and Discontinuation of Other Anticataplectic Medications - Dauvilliers, Yves; Šonka, Karel; Bogan, Richard K; Partinen, Markku; Del Rio Villegas, Rafael; Foldvary-Schaefer, Nancy; Skowronski, Roman; Chen, Abby; Black, Jed; Skobieranda, Franck; Thorpy, Michael J (CNS drugs, 2022)
BACKGROUND: Lower-sodium oxybate (LXB) is an oxybate medication with the same active moiety as sodium oxybate (SXB) and a unique composition of cations, resulting in 92% less sodium. LXB was shown to improve cataplexy and excessive daytime sleepiness in people with narcolepsy in a placebo-controlled, double-blind, randomized withdrawal study (NCT03030599). Additional analyses of data from this study were conducted to explore the effects of LXB on cataplexy, including the clinical course and feasibility of transition from other anticataplectics to LXB monotherapy. OBJECTIVE: The aim of these analyses was to evaluate cataplexy frequency during initiation/optimization of LXB and taper/discontinuation of prior antidepressant/anticataplectic medications. METHODS: Eligible participants (adults aged 18-70 years with narcolepsy with cataplexy) entered the study taking SXB only (group A), SXB + other anticataplectics (group B), or anticataplectic medication other than SXB (group C), or were cataplexy-treatment naive (group D). LXB was initiated/optimized during a 12-week, open-label, optimized treatment and titration period (OLOTTP). Other anticataplectics were tapered/discontinued during weeks 3-10 of OLOTTP. A 2-week stable-dose period (SDP; during which participants took a stable dose of open-label LXB) and 2-week double-blind randomized withdrawal period (during which participants were randomized to continue LXB treatment or switch to placebo) followed OLOTTP. Treatment-emergent adverse events (TEAEs) were recorded throughout the duration of the study. RESULTS: At the beginning of OLOTTP, median weekly cataplexy attacks were lower in participants taking SXB at study entry (SXB only [2.00]; SXB + other anticataplectics [0.58]) versus participants who were taking other anticataplectics (3.50) or were anticataplectic naive (5.83). Median weekly cataplexy attacks decreased during weeks 1-2 of OLOTTP in all groups. Increased cataplexy frequency was observed in participants tapering/discontinuing other anticataplectics during weeks 3-10 and was more prominent in participants taking other anticataplectics alone compared with those taking SXB plus other anticataplectics. Cataplexy frequency decreased throughout initiation/optimization in anticataplectic-naive participants. Median number of cataplexy-free days/week at the end of SDP (study week 14) was similar in all groups (6.0, 6.1, 6.0, and 6.2 in groups A, B, C, and D, respectively). During OLOTTP and SDP, TEAEs of worsening cataplexy were reported in 0%, 47.8%, 16.7%, and 2.2% of participants in groups A, B, C, and D, respectively; most TEAEs of worsening cataplexy were reported during tapering/discontinuation of other anticataplectics. CONCLUSIONS: LXB monotherapy was effective in reducing cataplexy and increasing cataplexy-free days. These results illustrate the feasibility of switching from SXB to LXB while tapering/discontinuing other anticataplectics. TRIAL REGISTRATION: A Study of the Efficacy and Safety of JZP-258 in Subjects With Narcolepsy With Cataplexy; https://clinicaltrials.gov/ct2/show/NCT03030599 ; clinicaltrials.gov identifier: NCT03030599.
Keywords: dospělí; Narcolepsy; Humans; lidé; poruchy nadměrné spavosti; kataplexie; dvojitá slepá metoda; Disorders of Excessive Somnolence; Double-Blind Method; Sodium Oxybate; oxybát sodný; Cataplexy; Adult; narkolepsie